Interpretasi Hermeneutik Karakter Kewirausahaan dalam Novel: Kontribusi Interdisipliner bagi Perkembangan Studi Sastra dan Kewirausahaan di Masa Depan - Asman Asman; Julia Marfuah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to interpret entrepreneurial characters in novels as cultural constructs embedded with values and ideology. Through a hermeneutical approach, literary works are understood as social discourses that reflect societal value systems, rather than merely aesthetic products. The study responds to the limitations of normative approaches in entrepreneurship education, which often emphasize practice and outcomes, by highlighting the importance of symbolic and narrative dimensions in literary texts. A qualitative method employing hermeneutic text analysis was applied to two novels by Asma Nadia: Bidadari untuk Dewa and Cinta Dua Kodi. Data were collected through close reading, literature review, interpretive validation, narrative excerpt classification, and categorization based on entrepreneurial character indicators. The findings reveal seven dominant entrepreneurial traits: responsibility, risk-taking, achievement motivation, self-confidence and optimism, collaboration, creativity and innovation, and leadership. Using the hermeneutic circle method, each trait was analyzed as a construction of meaning, emerging not only from narrative progression but also from the symbolic interaction between text and reader. These narratives show that entrepreneurial characters in the novels are shaped by the tension between personal idealism, religious values, and socio-economic dynamics. In-depth interpretation of dialogues, monologues, and dramatic situations enables a comprehensive reading of entrepreneurial actions as representations of cultural and spiritual identity. This research contributes to the interdisciplinary integration between literature and entrepreneurship studies by emphasizing the narrative dimension in shaping entrepreneurial character. The results demonstrate that literary texts can serve as reflective media in entrepreneurship education to foster ethical, resilient, and value-oriented entrepreneurial mindsets. The study recommends the strategic use of literature as a pedagogical tool to enrich value-based approaches in entrepreneurship development.